1991
DOI: 10.7589/0090-3558-27.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Avian Paramyxoviruses from Migrating and Resident Ducks in Coastal Louisiana

Abstract: Cloacal and tracheal swabs were collected from 1,409 hunter-killed ducks in Cameron Parish, Louisiana, during the 1986 and 1987 waterfowl seasons. Thirty avian paramyxoviruses (PMV's) were isolated from 605 blue-winged teal (Anas discors), 75 mottled ducks (A. fulvigula), 375 gadwalls (A. strepera), 334 green-winged teal (A. crecca), and 20 mallards (A. platyrhynchos). Prevalence of PMV decreased (P = 0.042) from September (4%) through November (2%) to December and January (1%). Juveniles had a higher prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…Banding data suggest that less than 2% of birds at Delaware Bay are juveniles less than 1 yr of age (Robinson et al, 2003). In wild ducks, the prevalence of AIV and APMV are highest in juveniles, a difference probably explained by increased disease susceptibility, or by an immunologically naive population (Hinshaw et al, 1985;Stallknecht et al, 1991). Hence, there is a possibility that the prevalence estimates presented by this (Harrington et al, 2007), were also found negative for APMV-1 and APMV-2.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Banding data suggest that less than 2% of birds at Delaware Bay are juveniles less than 1 yr of age (Robinson et al, 2003). In wild ducks, the prevalence of AIV and APMV are highest in juveniles, a difference probably explained by increased disease susceptibility, or by an immunologically naive population (Hinshaw et al, 1985;Stallknecht et al, 1991). Hence, there is a possibility that the prevalence estimates presented by this (Harrington et al, 2007), were also found negative for APMV-1 and APMV-2.…”
Section: Discussionmentioning
confidence: 89%
“…The most economically important serotype is APMV-1 (Newcastle disease virus), but other APMV serotypes have been isolated from domestic poultry, where they occasionally cause respiratory and reproductive disease (Warke et al, 2008). Information about the distribution of APMVs 2-9 in wild species is limited compared with APMV-1; however, all nine serotypes, except APMV-5, have been isolated from wild birds (Stallknecht et al, 1991;Hlinak et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to maximize its effectiveness, future monitoring should focus on collecting samples with the highest probability of virus detection. In addition to specie's factors (waterfowl and birds of prey have the highest antibody prevalence), other epidemiologic factors that must be considered, relative to NDV in wild birds, have been indicated (Stallknecht et al, 1991). These factors include age (juvenile birds show higher prevalence) and season of sampling (prevalence seems to drop from September to December).…”
mentioning
confidence: 99%
“…Although APMV-1 has been routinely isolated from wild ducks (Stallknecht et al 1991) and is associated with epidemics in Double-crested Cormorants (Phalacrocorax auritus; Kuiken et al 1998), transmission mechanisms are poorly defined in wild birds. Environmental transmission through contaminated water is important in the maintenance of influenza A viruses (IAV) in waterfowl populations (Rohani et al 2009), and viral persistence in water is dependent on water temperature and pH (Brown et al 2009).…”
mentioning
confidence: 99%